AWS Python Computer Vision : From Zero - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Learn to use the AWS (Amazon Web Services) platfrom to perform Computer Vision with the Python Language. This video course takes you from zero and introduces you to using the AWS Rekognition Console, AWS Cloud Shell and AWS Cloud9 environment to build computer vision solutions. Topics include: * Using AWS Rekognition to do Celebrity Recognition, Text Detection, PPE Detection and Image Labeling * Setting up AWS Cloud Shell to use the AWS SDK * Doing S3 copies with the AWS command-line SDK * Setting up AWS Cloud9 for development * Configuring bashrc file for use with Python * Using IPython with the AWS Boto3 SDK * Using Python Click to create command-line tools with colorized output * Using Github Actions to test and lint a computer vision project.